International Financial Reporting Standards and Value Relevance of Accounting Information: A Mult-Institutional Perspectives from Nigeria Quoted Firms - Diepiriye, Davies Stanley (International Journal of Accounting & Finance Review, 2018)
This study examined the effect of International Financial Reporting Standards on value relevance of accounting information of quoted firms in Nigeria. The objective is to examine if International Financial Reporting Standards affect value relevance of accounting information. The study focus on the commercial banks, manufacturing firms, insurance, government agencies and the oil and gas firms, questionnaires were structured and administered to accountants and finance managers. The data analyses adopted was the simple percentages and correlation coefficient. The results found a coefficient of 85.1 %, R2   and adjusted R2   of 60.3% and 51.4 %. We conclude that there is significant relationship between International Financial Reporting Standard and value relevance of accounting information   of quoted firms in Nigeria. We therefore recommend full compliance to the International Financial Reporting Standard, audit firms should adopt fully the International Financial Reporting Standard and Nigerian accounting bodies such as Institute of Chartered Accountants of Nigeria and Association of National Accountants of Nigeria should endeavor to encourage the auditing firms on the relevance of adopting International Financial Reporting Standard.